BRAIN NETWORK MODULATION WITH NON-INVASIVE BRAIN STIMULATION. Issue 12 (15th November 2016) - Li, Lucia; Violante, Ines; Ross, Ewan; Leech, Rob; Hampshire, Adam; Carmichael, David; Sharp, David
Abstract : Background: Transcranial direct current stimulation (tDCS) non-invasively delivers weak electrical currents cranially and can modulate cognition. However, translation into clinical use is difficult unless the neural basis of its actions is understood. Objectives: To investigate the effect of tDCS on brain network activity, including its interaction with: (i) brain state; and (ii) stimulation type. Methods: 12 healthy controls underwent simultaneous functional (f) MRI-tDCS. Participants performed a speeded response task (CRT) or 'rested' whilst having short duration (35 s) anodal, cathodal or sham stimulation to the right inferior frontal gyrus (rIFG), an area important for cognitive control. Results: Cognitive control requires balanced activity between two brain networks: the frontoparietal control network (FPCN) and default mode network (DMN). FPCN activity increases with externally focussed attention, whereas DMN activity increases with internally directed attention. These patterns were observed when switching between CRT and 'rest'. rIFG stimulation enhanced the networks associated with each cognitive state e.g. increasing FPCN and decreasing DMN activity during CRT. Furthermore, changes in network activity depended on tDCS polarity: cathodal tDCS produced greater activation within the FPCN. Conclusions: Abnormal network activity is seen in disordered cognition. These results suggest that rIFG tDCS could normalise network activity and may assist cognitive rehabilitation.